Exploratory Data Analysis on Mathematics Learning Difficulties for Junior High School Students/MTs on Solving Story Problems in Terms of Gender - Yusnita, Irra; Sumarmo, Utari; Fitriani, Nelly ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Mathematics subjects at various levels of education are still considered difficult. One of the mathematical skills that students still lack mastery of is mathematical communication. Otherwise in mathematics learning, as explained in NCTM, "communication is a fundamental element of mathematics learning," which means that communication is a basic element in mathematics learning. Mathematical story problems are a form of problem in mathematical communication competence. Moreover, based on the PISA report, with low language skills, students' ability to solve story problems also becomes much more difficult. This purpose study are to indentify and analyze the difficulties of junior high school students in solving math story problems and alternatives to overcome them, and also demography analyze these difficulties based on gender, age and elementary school educational background. Utilizing an Exploratory Data Analysis (EDA) approach, data were collected from 291 students in grades 7, 8, and 9. The findings indicate that most students struggle with understanding the text of word problems, identifying relevant information, and modelling mathematical problems. Further analysis reveals that 9th-grade students, particularly those older, encounter more complex challenges but demonstrate better problem-solving abilities. Gender differences were observed in learning strategies, with female students tending to use more structured strategies such as note-taking or diagramming.